Habitat Use by Different Size Classes of Bowhead Whales in the Central Beaufort Sea during Late Summer and Autumn - Koski, William R.; Miller, Gary W. (ARCTIC, 2009)
The frequency distributions of bowhead whale (Balaena mysticetus) size classes were studied as functions of year, location, water depth, and date. Whales were classified by size and status as calves, small subadults (non-calves < 10 m); large subadults (10–13 m); and adults (> 13 m). Adults include mothers with calves, which were also counted separately. During mid-August to early October of 1982, 1984–86, and 1998–2000, calibrated vertical photography was used to obtain known-scale images of 901 different whales in waters up to 200 m deep between Flaxman and Herschel islands (146? to 139? W) in the central Beaufort Sea. Age composition of the whales photographed over all years of our study was calves 6.2%, small subadults 31.4%, large subadults 33.3%, and adults 29.1%. We found proportionally more subadults and fewer adults than are estimated to be in the overall population, and this result was found both before and after making allowance for reduced effort to obtain photographs early and late in the migration period. Thus parts of the central Beaufort Sea up to 200 m deep appear to be more heavily used by subadult bowheads than by adults in most years. Significant interannual variation existed in length-frequency distributions of whales among years, geographic subdivisions of the study area, water depth categories, and time periods. This variation was due to variable use of the study area by each size class in different years, differences in the water depths used by different size classes, and different migration timing by each size class. In all years, small subadult whales were the dominant group in shallow (< 20 m) nearshore habitats, and the size of the whales increased with increasing water depth. Timing of movements into and through the study area were also related to size class: small subadults arrived first in late August and departed in late September, and adults arrived last in late September. Mothers and calves arrived in early September and were common until at least early October. La ...